Genomic and phenotypic characterization of Borrelia afzelii BO23 and Borrelia garinii CIP 103362. - Sébastien Bontemps-Gallo; Kevin A Lawrence; Crystal L Richards; Frank C Gherardini (PLoS ONE)
In recent years, the number of Lyme disease or borreliosis cases in Eurasia has been dramatically increasing. This tick-borne disease is caused by Borrelia burgdorferi sensu lato, which includes B. burgdorferi sensu stricto, the main species found in North America, and B. afzelii and B. garinii, which are primarily responsible for the disease in Eurasia. Currently, research on Lyme disease has focused mainly on B. burgdorferi while B. afzelii and B. garinii, which cause disease with distinctly different symptoms, are less studied. The purpose of this study is to evaluate B. afzelii BO23 and B. garinii CIP 103362 as model organisms to study Eurasian Lyme disease. To begin our analyses, we sequenced, annotated the chromosomes of both species and compared them to B. burgdorferi strain B31. We also assayed shuttle vector, pBSV2, for transformation efficacy and demonstrated that these strains can be cultured on solid media. In addition, we characterized how physicochemical parameters (e.g., oxygen, osmolarity, oxidative stress) affect both growth and motility of the bacteria. Finally, we describe each strain's antibiotic susceptibility and accessed their ability to infect mice. In conclusion, B. afzelii BO23 was more practical for in vitro and in vivo studies than B. garinii CIP 103362.